Pros and Cons of `Backing Winners' in Innovation Policy - Frank A.G. den Butter; Seung-gyu Jo (Tinbergen Institute, 2009)
In the economics profession there is a fierce debate whether industrial and innovation policy should be targeted to specific sectors or firms. This paper discusses the welfare effects of such targeted policies from the perspective of strategic game theory of the firm. A theoretical case for picking winners through a preferential innovative policy is discussed in a third-market international trade model, which is shown to hold without evoking retaliation from foreign competitors. However, in practice information uncertainties remain a concern. The question whether in this case `backing winners' is a wise policy option depends on the characteristics of the information asymmetries and on the extent the government is able to design selection procedures which minimize the transaction costs that may be caused from the market participants' opportunistic behavior.
Keywords: C73; F12; O24; O32; 330; Innovation policy; R&D subsidies; strategic trade policy; asymmetric information; spill-over effects; Innovationspolitik; Asymmetrische Information; Spillover-Effekt; Technologiewahl; Außenwirtschaftspolitik; Ökonomischer Anreiz; Mechanismus-Design-Theorie; Spieltheorie